Inteligencia emocional y su relación con el desempeño docente de una Institución Educativa, Iquitos 2024 - Tulumba Tuesta, Fernando David (2025)
The purpose of this research was to determine how emotional intelligence is related to teaching performance in an educational institution, 2024. Opting for a study of basic type, correlational level and non-experimental cross-sectional design; the sample consisted of 30 teachers for the survey conducted by a questionnaire for data collection. The findings show that there is a significance of p=0.003 between the variables. Likewise, the self-knowledge dimension shows a significance of p=0.002; similarly, the self-regulation dimension shows a significance of p=0.001; empathy shows a significance of p=0.003; and finally, the social skills dimension shows a significance of p=0.002; these dimensions are positively and significantly related to teaching performance.